The Museum Outside Museum - Giovanna Nichilò; Carla Langella (DIID, 2024)
Science museums have the important cultural mission of mentoring society in scientific and technological progress. To pursue this objective many resources have been invested in digital communication and marketing, but this is not sufficient to reach audiences that are not engaged with scientific culture.  To overcome the challenge of attracting uninterested visitors, some museums have chosen to extend their outreach beyond physical walls occupying highly frequented public spaces. This approach aims to capture the attention of citizens through exhibits and environments that encourage curiosity, entertainment, exploration, creativity, and social connection. By reviewing the international literature and project examples in this field, the paper proposes new audience development strategies for science museums to rethink the relationship between museums and society through a “museum outside the walls” inclusive perspective.